2021
DOI: 10.1093/sleep/zsab072.653
|View full text |Cite
|
Sign up to set email alerts
|

655 The Role of Insomnia Symptoms in the Relation between Perceived Vulnerability to Disease and COVID-19 Anxiety

Abstract: Introduction Individuals who report greater perceived vulnerability to disease (e.g., experience emotional discomfort to situations where pathogen transmission is likely) also have the tendency to endorse more anxiety. Insomnia is also associated with greater anxiety. This study assessed (1) whether perceived vulnerability to disease was associated with increased anxiety related to COVID-19 and (2) whether this association was moderated or mediated by insomnia symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study found that PVD can positively predict anxiety level, which is consistent with previous research results. 28 Studies have shown that individual cognitive differences lead to differences in perceived disease risk. 14 As a cognitive factor, PVD may change emotional states by influencing individual social cognition and corresponding behavioral responses.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that PVD can positively predict anxiety level, which is consistent with previous research results. 28 Studies have shown that individual cognitive differences lead to differences in perceived disease risk. 14 As a cognitive factor, PVD may change emotional states by influencing individual social cognition and corresponding behavioral responses.…”
Section: Discussionmentioning
confidence: 99%